PENGELOLAAN TAMAN BUDAYA PADA UPT MUSEUM DAERAH DAN TAMAN BUDAYA PROVINSI RIAU - Tanjung, Novia Rizky; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Management of cultural park is very important. Cultural park is a place to do activities related to art and culture. Riau province has a Cultural Park managed by Technical Implementation Unit (TIU) Regional Museum and Cultural Park Riau province, as a government institution responsible for the existence and development of local culture.for that institution, is required to do the development and cultural development of 12 districts or cities in riau province. Based on field observations, the problems that occur are some work programs that have been planned has not been implemented optimally. The purpose of this study is to know the management of cultural park and the factors that influence the management of cultural park at TIU Regional Museum and Cultural Park Riau province. The theory concept used is management according to George R.Terry which starts from planning, organizing, actuating, and controlling. This study used descriptive qualitative method. The type of data used is primary data and secondary data. Data collection research using observation techniques, interviews and documentation. Interviews were conducted with research informants such as Head of Cultural Service, Head of TIU Regional Museum and Cultural Park, Head of Culture Park Section, Riau Cultural Park employee and Artist. Conclusion of this research that management of cultural park at TIU Regional Museum and Cultural Park not yet optimal. There are still some shortcomings, especially in organizing, actuating, and controlling work programs. As well as the factors that influence the form of human resources, facilities and budget management of cultural park at TIU Regional Museum and Cultural Park. Keywords: Management, Organization, Cultural Park .